1974
DOI: 10.1177/00220345740530041501
|View full text |Cite
|
Sign up to set email alerts
|

Mineral Composition of Normal Human Enamel and Dentin and the Relation of Composition to Dental Caries: I. Macrominerals and Comparison of Methods of Analyses

Abstract: The macromineral concentrations in enamel and dentin from 175 permanent, sound teeth were related to age, sex, and number of DMFT in the patients. Calcium, phosphorus, chlorine, and potassium concentrations were greater in enamel than in dentin, but magnesium was higher in dentin. Analytical methods were compared for four elements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1
5

Year Published

1980
1980
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 9 publications
1
13
1
5
Order By: Relevance
“…The great variation in the amount of fluoride observed in sound dentin among the samples has also been noted by others. However, the concentration of fluoride observed in the present study was higher than that in other studies done in the 1970s (7)(8)15), perhaps due to the increased availability of fluoride. Furthermore, our samples were obtained from an area with a fluoridated water supply where there was access to fluoride dentifrice, whereas the samples used in other studies (7)(8)15) were collected from non-fluoridated areas where access to fluoride dentifrice was probably limited.…”
Section: Discussioncontrasting
confidence: 91%
See 2 more Smart Citations
“…The great variation in the amount of fluoride observed in sound dentin among the samples has also been noted by others. However, the concentration of fluoride observed in the present study was higher than that in other studies done in the 1970s (7)(8)15), perhaps due to the increased availability of fluoride. Furthermore, our samples were obtained from an area with a fluoridated water supply where there was access to fluoride dentifrice, whereas the samples used in other studies (7)(8)15) were collected from non-fluoridated areas where access to fluoride dentifrice was probably limited.…”
Section: Discussioncontrasting
confidence: 91%
“…Calcium, inorganic phosphate and fluoride are the main constituents of the mineral phase of dentin (2,(7)(8)(9). The concentrations of these ions play an important role in the processes of demineralization and remineralization of dentin (3)(4)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, Derise et al (1974) reported that the mean concentration of Ca and P were 37.1 and 18.1% in the permanent teeth enamel, while Lakoma and Rytomaa (1977) did not observed differences in the amount of theses ions between primary and permanent teeth enamel. The different values of Ca and P reported in the current study may be due to factors such as the region where the teeth were collected, variations between individual teeth, the type, age and ethnicity and even the methodology performed at the researches.…”
Section: Discussionmentioning
confidence: 88%
“…Em nosso estudo encontramos os valores médios dos elementos quími-cos da dentina em que o cálcio correspondeu a 34,29% e o fósforo a 20,42% (Quadro 3) O valor médio de porcentagem observado em estudos da dentina de dentes permanentes humanos foi entre 26,7% e 50,77 para cálcio e 13,6% a 18,2% para o fósforo (Derise 1974, Oliveira et al 2010. Diante disso, observamos mais uma vez similaridade de nossos resultados com os valores descritos na literatura para dentes humanos.…”
Section: Discussionunclassified